Effect of aerobic performance level on the maximal lactate steady state determined during intermittent protocol in swimming - Greco, C. C.; Mendes de Oliveira, M. F.; Caputo, F.; Pelarigo, J. G.; Denadai, B. S. (Revista Brasileira de Medicina do Esporte, 2010)
Endurance athletes frequently perform intermittent exercises with the aim to increase training intensity. A very important index in the evaluation of these athletes is the maximal lactate steady state (MLSS), which is usually determined by a continuous protocol. However, the interruptions during intermittent exercise may alter the metabolic conditions of the exercise. The objective of this study was to compare the intensity at MLSS determined by continuous (MLSSc) and intermittent protocols (MLSSi) in athletes with different aerobic performance levels. Twelve male swimmers (22 ± 8 years, 69.9 ± 7.6 kg and 1.76 ± 0.07 m) and eight male triathletes (22 ± 9 years, 69.5 ± 10.4 kg and 1.76 ± 0.13 m) performed the following tests on different days in a 25 m swimming pool: 1) 400 m performance test (v400) 2) 2 to 4 repetitions with 30 min duration at different intensities to determine MLSSc, and 4) 2-4 repetitions of 12 x 150 s with an interval of 30 s (5:1) at different intensities to determine MLSSi. The swimmers showed v400 (1.38 ± 0.05 and 1.26 ± 0.06 ms-1, respectively), MLSSc (1.23 ± 0.05 and 1.08 ± 0.04 ms-1, respectively) and MLSSi (1.26 ± 0.05 and 1.11 ± 0.05 ms-1, respectively) values higher than triathletes. However, the percentage difference between MLSSc and MLSSi was statistically similar between groups (3%). There was no difference between blood lactate concentration at MLSSc and MLSSi in either group. Based on these results, it can be concluded that the intermittent exercise used enables increase in the exercise intensity at MLSS, without change in lactate concentration regardless of the aerobic performance level.